Use of R. carthamoides in feeding black-and-white cattle heifers - I. N. Zhdanova; N. A. Morozkov (Аграрная наука Евро-Северо-Востока, 2022)
The article presents the results of studies on the effect of feeding doses of vitamin-herbal flour made of the green mass of R. carthamoides on the growth dynamics and biochemical composition of the blood of young cattle. The studies were carried out in 2022 at the dairy complex of Sokolovo LLC (Perm Krai). The objects of the study were replacement heifers of the Holsteinized Black-and-White breed at the age of 12-15 months. For 92 days, heifers of I and II experimental groups were additionally fed vitamin-herbal flour made of R. carthamoides in the dose of 150 and 300 g per head per day as part of the main diet. The use of nitrogen from the incoming and from the digested one was more in heifers of the I and II experimental groups by 0.74-1.09 %abs. (p < 0.05) and 2.17-3.64% abs. (p < 0.01) compared with the control group. At the age of 15 months, heifers of I and II experimental groups in terms of live weight exceeded the animals of the control group by 2.80 and 18.20 kg (p < 0,001) by asbsolute gain by 4.86 and 11.61% respectively. At the end of the experimental period, in the blood serum of heifers of the II experimental group, where the maximum dose of vitamin-herbal flour was used, the content of total protein increased by 11.43 %, albumin ‒ by 14.01 %, carotene - by 28.57 %, the level of reserve alkalinity ‒ by 18.01 %. In all cases, the difference with the control was confirmed statistically (p < 0.05-0.001). Thus, the studies carried out testify to some bioavailability of vitamin-herbal flour and its positive effect on the physiological state of experimental animals, which consists of the normalization of metabolism and improvement of biochemical parameters of blood, which makes it possible to recommend introducing vitamin-herbal flour made of R. carthamoides into the diets of young cattle at the rate of 300 g per head per day.